An Wonderful Summation Formula of Half Argument Involving Contiguous Relation (Global Journal of Science Frontier Research, 2014)
In this paper we have developed a summation formula of half argument involving recurrence relation of Gamma function and contiguous relation.
Keywords: gauss second summation theorem; recurrence relation; contiguous relation